Freed from Sadness and Fear: Politics, COVID-19, and the New Germany. Issue 3 (1st September 2021) - Meng, Michael; Seipp, Adam R.
Abstract: This article argues that we are witnessing the possible emergence of a Germany confident in the strength of its rational and democratic approach to governance. Thinking about this development through Baruch Spinoza's insights into the centrality of reason to democracy, we suggest that Germany has responded to its past in a salutary manner by building a rational and responsible democracy. Few recent events illustrate this transformation more clearly than Germany's reaction to the covid -19 pandemic.